Caracterização físico-química e de compostos bioativos de folhas de batata-doce comum e biofortificada (Ipomea batatas L.) - Fagundes, Maria Elisabete (2020)
Biofortification is a strategy to combat malnutrition. It can be done with the crossing of plants of the same species to generate more nutritious cultivars, better known as genetic improvement, in order to enrich one or more essential micronutrients, such as iron, zinc, calcium and vitamin A. An example of these biofortified foods are the Beauregard sweet potatoes, which can be eaten in their entirety (root, stem and leaves). It is a cultivar that has orange flesh, which has a greater amount of beta-carotene, a precursor of vitamin A, having an essential role in the human body, such as disease prevention, growth and development and strengthening of the immune system, as well as acting as an antioxidant, fighting free radicals. Sweet potato leaves are an excellent food and can be eaten cooked, as a flour in the preparation of food and tea, and raw, prepared as a salad rich in nutrients and bioactive compounds such as anthocyanins and polyphenols. This work aimed to compare the physical-chemical composition of bioactive compounds and the antioxidant potential present in Rubissol and biofortified sweet potato leaves (Beauregard cultivar). A completely randomized design (DIC) was used, with two treatments (common and biofortified sweet potato leaves) and six repetitions, in a total of 12 experimental parcels. The results obtained were submitted to statistical evaluation. The level of significance considered was 5%. The partial average results, of the physical-chemical compositional analyzes, indicated average percentages for the protein contents of 28.98% and 28.41%, for common and biofortified sweet potato leaves, respectively. In the determination of total fibers, the average values found were 24.56% and 28.07%, for the Beauregard and Rubissol sweet potato leaves, respectively. The concentrations of bioactive compounds between Rubissol and Beauregard cultivars were: 13.20 and 120.33 µg / g (total carotenoids), 65.23 and 78.71 mgCE / 100g (flavonoids), 3.24 and 9.37 mg / 100g (anthocyanins), 196.04 and 269.43 mgEAG / 100g (total phenolics), 192.27 and 132.23 g / g DPPH (antioxidant activity). Considering the composition of the two sweet potato leaf varieties evaluated in this research, it is possible to highlight the nutritional importance and relevance in bioactive components of this usually discarded part of the plant when compared to the roots, that are commonly consumed, and also, evidence the possibility of its introduction into human food.